The Effect of Financial Literacy, Digital Literacy, and Information Security on QRIS Adoption among Students in Banten - Judijanto, Loso; Husnayetti, Husnayetti (West Science Accounting and Finance, 2024)
This study investigates the impact of financial literacy, digital literacy, and information security on the adoption of Quick Response Code Indonesian Standard (QRIS) among students in Banten. Utilizing a quantitative research methodology, data were collected from a sample of 170 students using Likert scales ranging from 1 to 5. Structural Equation Modeling-Partial Least Squares (SEM-PLS 3) was employed for data analysis. The results indicate that all hypothesized relationships are positive and significant. Specifically, financial literacy (β = 0.323, t = 5.633, p = 0.002) significantly enhances QRIS adoption, suggesting that students with higher financial literacy are more likely to adopt QRIS. Digital literacy (β = 0.848, t = 30.753, p < 0.001) also shows a significant positive effect, indicating that students proficient in digital technologies are more inclined towards QRIS adoption. Additionally, information security (β = 0.695, t = 9.446, p < 0.001) significantly influences QRIS adoption, underscoring the importance of secure information practices in fostering the adoption of QRIS among students. The findings underscore the critical roles of financial and digital literacy, alongside robust information security, in promoting QRIS adoption within the student demographic in Banten. These insights provide valuable implications for educators, policymakers, and financial institutions aiming to enhance the adoption of digital payment systems.